Antimicrobial activity of nanoparticles : applications in wound healing and infection treatment - Guisbiers, Gregory (Advanced topics in biomaterials, 2023)
Antimicrobial Activity of Nanoparticles: Applications in Wound Healing and Infection Treatment presents the state of the art among nanotechnological approaches used in the treatment of infections. This field has gained a large amount of interest over the past few years, in response to the increasing resistance of pathogens to antibiotics. Leading researchers from around the world discuss the synthesis routes of nanobiomaterials, characterization, and their applications as antimicrobial agents. The book covers various aspects: from antiviral and antibacterial nanoparticles, to the functionalization of nanoparticles and their toxicity to human cells. This book offers an advanced reference text for biomedical engineers, materials scientists, clinicians, and biochemists, with an interest in nanomedicine and infection control.